SELECTION AND EVALUATION OF DIVERSE SUGARCNE GENOTYPES IN 4TH STAGE - M. Chohan; U. A. Talpur; S. Junejo; G. S. Unar; R. N. Pahnwar; I. B. Bhatti (Journal of Animal and Plant Sciences, 2014)
Comparative performance of 12 sugarcane genotypes were tested in 4th stage against two local check varieties at National Sugar Crops Research Institute, Thatta. Study aimed at to identify potential sugarcane genotypes for releasing them as new commercial varieties in future. Genotypes under evaluation were developed from bi parental cross of USA origin fuzz (true seed). The experiment was laid out using a triplicate Randomized Complete Block Design (RCBD). Significant differences among the genotypes were observed for cane yield and contributing parameters and sugar yield. Plant crop attained more cane yield, CCS% and sugar yield as compared to ratoon crop. The traits i.e. cane height and millable canes for plant crop while, cane girth and millable canes for ratoon crop showed strong significant relationship for enhancing cane yield. Insect pest infestation stated that attack in ratoon crop was remained 20.32% higher than plant crop. Stem borer accounted high infestation followed by top and root borer among the genotypes. The genotypes HoTh-402, HoTh-404, HoTh-408, HoTh-409, HoTh-414 and HoTh-430 on account of their better performance were selected for further testing and progression in final selection trials. The selected genotypes have great promise to be good commercial varieties in future.
Keywords: Genotypes; Saccharum officinarum; sugarcane; cane yield; CCS%; insect pest infestation